THE INTEGRATED PRACTICE OF THE INTENSIVE PHYSIOTHERAPIST IN THE MULTIPROFESSIONAL TEAM - Marques Pereira Sales, Emanuela (2022)
The hospital environment is based on the integrality of care. Critically ill patients are treated in the Intensive Care Unit (ICU). The physiotherapist is part of the multiprofessional team and actively participates in the care of critically ill patients. To analyze the integrated practice of the physiotherapist as a member of the multiprofessional team in an Intensive Care Unit. Quantitative cross-sectional field study, carried out from August 2020 to September 2021, using an electronic questionnaire with 49 physiotherapists from two hospitals in Fortaleza.  Descriptive analysis of the collected data was used. Multiprofessional integration happened mainly in multidisciplinary visits, and the main impacts generated from multidisciplinary integration were: Improved communication, effectiveness of care and reduction of complications. Acting in COVID-19 promoted greater interprofessional contact. The physiotherapist plays an important active role as a member of the multiprofessional team in the ICU, offering individualized assistance and ensuring the effectiveness of multiprofessional care.